The second martyr, Sheikh Zainuddin bin Ali Al-Amili,Pioneer of educational reform (Journal of the College of Basic Education, 2023)
The scientific and intellectual movement began in Jabal Amel in the seventh century AH, the thirteenth century AD, based on a foundational stage in which the Amel scholars appeared, as they made the Imami thought in that spot a home and for other sciences in which there are many scientific centers. In a short period of time, it became a source and an exporter of science and scholars.The Jabal Amel renaissance emanated from its own scholars, despite the backwardness that afflicted our Islamic world, but the scholars of Jabal Amel continued their scientific work steady with determination and perseverance.One of these scientists was the second martyr, Sheikh Zainuddin bin Ali bin Ahmed Al-Amili, who was one of the pioneers of reform and one of the founders of the scientific and intellectual renaissance there, with what he embodied in form of of scientific personality, social morals, reform ideas, educational projects and valuable compositions in literature. He is considered one of the prodigies of the islamic nation in his scientific stature and virtue, and he prevailed, through his efforts and knowledge, in restoring the lost sectarian identity of the Shiites in Jabal Amel and the Levant, which was lost in the pool of political currents that opposed the Shiit sect, which was manifested in the intolerance of non-Sunni sects and the fight against other sects outside the Sunni sect which were prosecuted by authorities